Controladoria em instituição pública de ensino superior: Percepção do seu papel sob a ótica dos gestores da UNEMAT - Durigon, Almir Rodrigues (Universidade do Vale do Rio dos Sinos, 2012)
This study aims at identifying the perception of the managers of the University of the State of Mato Grosso - UNEMAT, about the performance of the controllership, observing whether the controllership is helping the managers of the institution in their activities aimed to the fulfillment of the institutional mission of meeting the demands of the State and of the society. The Controllership is an organ that gives support to the administration, providing information for the process of decision making that leads the organization to reach the planned results, contributing, thus, to its continuity. It is a descriptive and exploratory research, as it concerns to its goals, and involving quantitative and qualitative aspects in the approach of the problem. The collecting of data was made through instrument of research structured with assertive and scales of the type Likert of five points, whose applying occurred personally between the researcher and the managers of the current administration (2010-2014), during the 4 th quarter of 2011, and with the managers of the previous administration (2006- 2010) in the 2nd quarter of 2012. In some special situations that application occurred by e-mail. For the quantitative analysis of the data we used the mensuration medium ranking pondered of the scales, frequency, standard deviation, variation coefficient and correlation coefficient of Pearson (r). The respondents were pooled in managers of the rectory and coordinators of campi actuating in the periods of administration above mentioned. The main results show, under the viewpoint of the managers of both administrations, that: (a) the changes of the public administration may favor the development of the institution, however, they also realize that it is still pointed to the fulfillment of budget; (b) the controllership of UNEMAT, is an area that contributes to the straightening and development of the institution, however it is necessary to know its applicability better; (c) the lack of a more suitable material and human structure compromises the development of the activities with effectiveness; (d) the controllership needs to act more strictly in helping the elaboration of the budget, financial analyses, evaluation of results and management control, as well as in the planning of the process of administration of the university; (e) it was clear the distancing of the coordinators of campi from the acting of the controllership, aspect that needs observing by the administration. There is a general recognition that the controllership can advance a lot in its activities and contribution to the administration of the IPES, since it is still with strong legal bias of internal control.
Keywords: Gestão pública; Controladoria; Instituição pública de ensino; Public administration; Controllership; Public institution of teaching; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis